Mencari Alternatif Strategi Pemberantasan Korupsi - Agus Pramusinto (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2009)
This paper discusses an alternative strategy to combat corruption in Indonesia. Various approaches previously adopted such as law enforcement and administrative reform are not effective enough. The result of reducing corruption is not satisfactory as evidence that level of corruption in the country remains high. Therefore, a cultural approach is needed to supplement the exiting ones. By introducing an anti corruption culture through education, we hope that people will become aware of the danger of corruption and prevent themselves from being involved in corrupt practices. This method should be adopted from early time in the kindergarten and elementary school.